2010
DOI: 10.1080/07900627.2010.519519
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Rainfall Variability: Dry Spell Mitigation and Implication on Landscape Water Balances in Small-scale Farming Systems in Semi-arid Niger

Abstract: Rainfall variability and inherent dry spells are a reality with severe implications for smallholder agro-ecosystems in semi-arid Sahel. To increase both on-and off-farm biomass production and productivity is challenging with these climate-induced temporal and spatial variations of water. This paper tests the idea that increased vegetation through tree cover may impact water balance in a water-stressed landscape: South-east Niger. Local rainfall data, farming systems data and a landscape water-modelling tool (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Dry spells cause green water scarcity without necessarily causing reductions in seasonal or annual rainfall [20]. In field studies in the Sahel, Rockström [21] showed that dry spells disturb the root uptake capacity, which can result in large evaporation losses and therefore low yields [22].…”
Section: (Iii) Dry Spellsmentioning
confidence: 99%
“…Dry spells cause green water scarcity without necessarily causing reductions in seasonal or annual rainfall [20]. In field studies in the Sahel, Rockström [21] showed that dry spells disturb the root uptake capacity, which can result in large evaporation losses and therefore low yields [22].…”
Section: (Iii) Dry Spellsmentioning
confidence: 99%
“…Nevertheless, the presented results agree with recent findings in the literature and can therefore be assumed to correspond to a general tendency. Also, Barron et al (2010) and Balme et al (2006) both indicated a recovery of the total rainfall amount at the end of the 20th century in the region, and respectively point out an increase in dry spell occurrence and a decrease in the number of rainfall events. We were unfortunately unable to determine from these data whether the general tendency of an increasingly erratic rainfall distribution was uniquely caused by climate change, as in addition to climate change, land use change might also drive or enhance changes in rainfall distribution by deforestation or by increasing human agricultural exploitation, leading to land degredation (IPCC 2007;Mahé and Paturel 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Yet these droughts were not unprecedented, as the Sahel has historically always witnessed alternating humid and arid periods (Nicholson 2001;Mishra and Singh 2010). More recent studies in fact speculate about a shift toward a less arid state and about rainfall recovery with wetter years from the 1990s onward (Greene et al 2009;Nicholson 2005;Balme et al 2006;Mahé and Paturel 2009;Barron et al 2010;Elagib 2010). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It governs the crop yields and determines the choice of the crops that can be grown (Tesfaye & Walker 2004b;Lansigan 2005). Therefore, a detailed knowledge of rainfall behaviour which includes information concerning the trends or changes of precipitation (Osman & Sauerborn 2002;Admassu et al 2007a;Cheung et al 2008); the start, end and length of the growing period (Camberlin & Okoola 2003;Marteau et al 2011) and the risk of dry and wet spells, is an important prerequisite for agricultural planning (Simane & Struik 1993;Tesfaye & Walker 2004a;Barron et al 2010).…”
Section: Agro-climatological Information: It's Role For Managing Riskmentioning
confidence: 99%